EFEKTIFITAS PIJAT BAYI TEKNIK KUNCI DAN SENAM BAYI TERHADAP PENINGKATAN NAFSU MAKAN BAYI USIA 6 - 12 BULAN DI PUSKESMAS KENJERAN SURABAYA. - Umi Ma'rifah; Gita Marini (Jurnal Keperawatan Muhammadiyah, 2016)
Objective:   The number of children under Indonesia is very large at around 10% of the entire population, the quality of growth and development of infants need to get serious attention is to get good nutrition. The provision of good nutrition depends on nutrition is also influenced by the consumption of a meal. The number of infants who have difficulty eating as much as 25%, an increase of 40-70% in children born prematurely or with chronic diseases in the region of Puskesmas Kenjeran Surabaya. Massage as an alternative to improve health by increasing underweight due to a decrease in appetite. Babies who do gymnastics baby talk faster, better appetite, sleep more soundly, and in the process of development of motion more quickly than babies who do not follow gymnastics.The study aims to analyze the effectiveness of infant massage techniques and exercise key to increased appetite infant infants aged 6-12 months in Puskesmas Kenjeran Surabaya.Methods: The study was conducted for 8 months. Research Design Pre experimental design pre-post test only. Its population is infants aged 6-12 months were decreased appetite ranging from mild to severe in the IHC area Kenjeran Surabaya health centers with a total sample of 25 infants using cluster random sampling techniqueResults:  The collection of data through questionnaires and observation. The results of the data analysis by Spearman Rho test result p = 0.029, which means that there is the effect of infant massage and baby gymnastics to increased appetite. Conclusion:  Infant massage combined with baby gymnastics can be applied to infants aged 6-12 months, so there is an increase in appetite, as well as solutions to improve the nutritional status of infants who weigh